Nanoparticle-allergen interactions mediate human allergic responses: protein corona characterization and cellular responses. Issue 1 (December 2015) - Radauer-Preiml, Isabella; Andosch, Ancuela; Hawranek, Thomas; Luetz-Meindl, Ursula; Wiederstein, Markus; Horejs-Hoeck, Jutta; Himly, Martin; Boyles, Matthew; Duschl, Albert
Abstract Background Engineered nanomaterials (ENMs) interact with different biomolecules as soon as they are in contact, resulting in the formation of a biomolecule 'corona'. Hence, the 'corona' defines the biological identity of the ENMs and could affect the response of the immune system to ENM exposure. With up to 40 % of the world population suffering from type I allergy, a possible modulation of allergen effects by binding to ENMs is highly relevant with respect to work place and consumer safety. Therefore, the aim of this present study was to gain an insight into the interactions of gold nanoparticles with different seasonally and perennially occurring outdoor and indoor allergens. Methods Gold nanoparticles (AuNPs) were conjugated with the major allergens of birch pollen (Bet v 1), timothy grass pollen (Phl p 5) and house dust mite (Der p 1). The AuNP-allergen conjugates were characterized by means of TEM negative staining, dynamic light scattering (DLS), z-potential measurements and hyperspectral imaging. Furthermore, 3D models were constructed, based on the characterization data, to visualize the interaction between the allergens and the AuNPs surface. Differences in the activation of human basophil cells derived from birch/grass pollen- and house dust mite-allergic patients in response to free allergen and AuNP-allergen conjugates were determined using the basophil activation assay (BAT). Potential allergen corona replacement during BAT was controlled for using Western blotting. The protease activity of AuNP-Der p 1 conjugates compared to free Der p 1 was assessed, by an enzymatic activity assay and a cellular assay pertaining to lung type II alveolar epithelial cell tight junction integrity. Results The formation of a stable corona was found for all three allergens used. Our data suggest, that depending on the allergen, different effects are observed after binding to ENMs, including enhanced allergic responses against Der p 1 and also, for some patients, against Bet v 1. Moreover elevated protease activity of AuNP-Der p 1 conjugates compared to free Der p 1 was found. Conclusion In summary, this study presents that conjugation of allergens to ENMs can modulate the human allergic response, and that protease activity can be increased. Graphical Abstract Cross-linking of IgE receptors and degranulation of human basophils due to epitope alignment of nanoparticle-coated allergens.